2019
DOI: 10.2337/dc19-1481
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Sodium–Glucose Cotransporter 2 Inhibitors in Patients With Type 1 Diabetes and Rates of Diabetic Ketoacidosis

Abstract: To estimate real-world off-label use of sodium-glucose cotransporter 2 (SGLT2) inhibitors in patients with type 1 diabetes, estimate rates of diabetic ketoacidosis (DKA), and compare them with DKA rates observed in sotagliflozin clinical trials. RESEARCH DESIGN AND METHODSWe identified initiators of SGLT2 inhibitors in the Sentinel System from March 2013 to June 2018, determined the prevalence of type 1 diabetes using a narrow and a broad definition, and measured rates of DKA using administrative claims data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 33 publications
0
37
1
Order By: Relevance
“…These characteristics were selected because they could be associated with directing drugs to a specific patient group. For example, some patients with type 1 diabetes in the US are prescribed SGLT2 inhibitors off label 19. Similar to the CANVAS Program, patients with a prior amputation were not excluded.…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics were selected because they could be associated with directing drugs to a specific patient group. For example, some patients with type 1 diabetes in the US are prescribed SGLT2 inhibitors off label 19. Similar to the CANVAS Program, patients with a prior amputation were not excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The U.S. Food and Drug Administration estimates that one additional case of ketoacidosis occurs every 26 years when patients with type 1 diabetes are treated with sotagli ozin. Assuming a case fatality rate of 0-4%, this estimate corresponds to 16 additional deaths per year per 100,000 patients with type 1 diabetes treated (31,32). Thus, although a reduction in basal insulin dose in SGLT2 inhibitor therapy in type 1 diabetes is bene cial in the prevention of hypoglycemia, there is a risk of increasing the risk of diabetic ketoacidosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Sotagliflozin, a dual inhibitor of sodium-glucose cotransporter 1 (SGLT1) and sodiumglucose cotransporter 2 (SGLT2), provides a contemporary example of how real-world data can be effectively considered during the drug approval process. 3,4 The first-discovered SGLT1/SGLT2 inhibitor was phlorizin. It is a naturally occurring glucoside found in the root bark of fruit trees and was first isolated in the late 1800s.…”
mentioning
confidence: 99%
“…1 The FDA did that exactly. 3,4 Using a distributed data network with data from over 100 million patients through the Sentinel Initiative, the FDA identified that up to 1% of prescriptions for SGLT2 inhibitors were for patients with type 1 diabetes. 3,4 In this population, the rate of DKA was about 7 per 100 person-years, and as high as 20 per 100 personyears among women aged of 25 to 44 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation